The Importance of Brand on B2B Markets Case Study of Hilti - Konečný, Martin (2013)
The brand is mostly associated with business-to-customer markets and environment. People would first think of such a brand, because we see marketing and advertising of those brands every day. But business-to-business brands are for companies also very important. The overall goal of my thesis would be to find out how the managers of a pure B2B company perceive the importance of brand in the B2B environment where the company operates. Theoretical part will, in the first chapter, characterize B2B environment as well as the specifics of brand building on this market. Second chapter focuses directly on the factors influencing brand success on B2B market and how brand influences and helps the company to succeed. Then, practical part is going to be focused on a company Hilti AG - a global premium provider of building construction tools and consumables in B2B, where the qualitative expert interviews with managers across different business units and departments -- marketing, sales and brand management -- will be conducted and will provide a base for my research.